Effectiveness of Internal Supervision of the Inspectorate of East Bolaang Mongondow Regency - Lukman, Riri; Kairupan, Sisca B.; Mokat, Jetty E. H.; Mandagi, Marthinus (Technium Social Sciences Journal, 2025)
This study aims to analyze and describe the effectiveness of internal supervision conducted by the East Bolaang Mongondow Regency Inspectorate in carrying out its oversight functions on government programs and activities. This research adopts a qualitative approach, utilizing both primary and secondary data sources. Data collection techniques include observation, interviews, and document analysis, while data analysis is conducted using an interactive model comprising data collection, data display, data condensation, and verification. Effective internal supervision is a critical element in ensuring accountable and transparent regional governance. The East Bolaang Mongondow Inspectorate, as the Government Internal Supervisory Apparatus (APIP), faces various challenges in implementing follow-ups on audit recommendations, including limited human resources, inadequate infrastructure support, and coordination issues among institutions. In 2023, 16.48% of audit recommendations remained unaddressed, with unresolved regional financial losses totaling IDR 29.3 billion. These findings highlight the need to enhance auditee compliance and strengthen internal control systems. The study reveals that while internal supervision has generally been conducted well, it encounters obstacles such as limited human resources, inadequate auditee responsiveness, and suboptimal inter-agency coordination. These factors affect the follow-up of audit recommendations, impacting the overall effectiveness of supervision. The study recommends improving human resource capacity, enhancing internal control systems, and strengthening inter-agency coordination to create more effective and efficient supervision.